Developing Metacognitive Skills Through N03R Learning - Nur Rokhman; Sukestiyarno Sukestiyarno; Rochmad Rochmad; Mulyono Mulyono (Universitas Negeri Semarang, 2022)
Students require metacognitive skills to reflect on what is being done, what is required in completing assignments, and selecting and implementing learning strategies that promote learning success. The development of metacognitive skills requires creative thinking and a systematic process in learning to solve mathematical problems, which has not been implemented optimally. This study aims to determine students' metacognitive skills through NO3R learning in solving mathematical problems. This study uses sequential exploratory mixed methods. Data was collected through tests, observation techniques, interviews, and documentation. The research subjects were 31 students who were asked to work on geometry problems. The researchers analyzed each student's work based on the NO3R learning stages. Furthermore, to clarify answers and explore students' metacognitive skills, in-depth observations and interviews were performed. The results showed that students' metacognitive skills in solving math problems were on high criteria. NO3R learning is effective for developing students' metacognitive skills. Metacognitive skills can be taught to students to develop their thinking so that their learning outcomes are better.